High rate of return to sport following abdominal muscle strain injuries in national collegiate athletic association division I overhead athletes—a case series - Bolia, I. K.; Weber, A. E.; Ihn, H.; Won, P.; Hasan, L. K.; Haratian, A.; Noceti-Dewit, L.; Romano, R.; Tibone, J. E.; Gamradt, S. C. (International Journal of Athletic Therapy & Training, 2022)
This case series describes the rate and time to return to sport following nonoperative management of abdominal muscle strain in the National Collegiate Athletic Association Division I. Twenty-seven overhead athletes were included, and each participated in a rehabilitation flexibility program as well as interventions addressing hip and thoracic rotational deficits. To our knowledge, this is the first study to report on the rates of abdominal injury in overhead athletes and their return to sport at a National Collegiate Athletic Association Division I institution. Volleyball athletes were disproportionately affected by abdominal injuries in the present study, and these injuries have been reported to account for up to 22.2% of muscle injuries in elite volleyball athletes. Similar to the finding in the present study, two baseball studies demonstrated that the abdominal musculature on the opposite side of the dominant arm (lead side) was usually affected.